Youla parameterized adaptive vibration control against deterministic and band-limited random signals. (1st December 2019) - Qian, Fanfan; Wu, Zhizheng; Zhang, Maotong; Wang, Tao; Wang, Yuanyuan; Yue, Tengfei
Highlights: A H ∞ controller with augmented Youla ( Q ) parameterized adaptive regulation approach is proposed to reject both random and deterministic vibrations. By incorporating Youla parameterization scheme into the controller, the internal model of the disturbances may implicitly be contained in the controller with the appropriately designed Q parameters. The parameter Q is converged to the desired value by online tune of a recursive least squares (RLS) algorithm based on the Internal Model Principle. An experimental evaluation on a lathe system has been carried out to indicate the effectiveness of this adaptive approach to attenuate both the band-limited random disturbance and the narrow-band unknown deterministic disturbance. Abstract: Multiple narrow band deterministic and band-limited random disturbance signals will occur during machining process, which will cause vibration and have negative effect on the cutting accuracy. For instance, in a lathe system, spindle rotation can produce narrow band deterministic vibration disturbance and turning process can lead to band-limited random vibration disturbance. In this paper, a H ∞ controller with augmented Youla ( Q ) parameterized adaptive regulation approach is proposed to reject both random and deterministic disturbances. The parameter Q is converged to the desired value by online tune of a recursive least squares (RLS) algorithm. An experimental evaluation on a lathe system has been carried out to indicate the effectiveness of this approach. The result illustrates that the proposed adaptive control method can effectively attenuate the lathe vibrations against the unknown deterministic and band-limited random disturbances.